(untitled) - Sestina, John E.; John E. Sestina (Hoboken, New Jersey, 2016)
Planning a Successful Future empowers advisors and clients to take control of their money and manage their income to achieve their financial goals. Written by the father of fee-only financial planning, this book features real-life stories and examples from over three decades in the industry to illustrate how financial planning works and the best way to create your strategy. You'll learn how to identify and prioritize your goals, and why they're important—and how to get where you need to be for retirement, education, home ownership, and more. Practical exercises get you started on the right track, and useful checklists keep you organized and focused along the way. You'll get expert insight on risk management, allocation, tax reduction, estate planning, and more, as you develop your strategy and put it into action
Keywords: Finance; Personal; Portfolio management; Financial planners